Electromagnetic Image-Guided Orbital Decompression: Technique, Principles, and Preliminary Experience with 6 Consecutive Cases. (December 2014) - Servat, Juan J.; Elia, Maxwell Dominic; Gong, Dan; Manes, R. Peter; Black, Evan H.; Levin, Flora
Abstract Purpose: To assess the feasibility of routine use of electromagnetic image guidance systems in orbital decompression. Methods: Six consecutive patients underwent stereotactic-guided three wall orbital decompression using the novel Fusion ENT Navigation System (Medtronic), a portable and expandable electromagnetic guidance system with multi-instrument tracking capabilities. The system consists of the Medtronic LandmarX System software-enabled computer station, signal generator, field-generating magnet, head-mounted marker coil, and surgical tracking instruments. In preparation for use of the LandmarX/Fusion protocol, all patients underwent preoperative non-contrast CT scan from the superior aspect of the frontal sinuses to the inferior aspect of the maxillary sinuses that includes the nasal tip. Results: The Fusion ENT Navigation System (Medtronic™) was used in 6 patients undergoing maximal 3-wall orbital decompression for Graves' orbitopthy after a minimum of six months of disease inactivity. Preoperative Hertel exophthalmometry measured more than 27 mm in all patients. The navigation system proved to be no more difficult technically than the traditional orbital decompression approach. Conclusion: Electromagnetic image guidance is a stereotactic surgical navigation system that provides additional intraoperative flexibility in orbital surgery. Electromagnetic image-guidance offers the ability to perform more aggressive orbital decompressions with reduced risk.